FROM STRUCTURALISM TO DECONSTRUCTION: TRACING THE EVOLUTION OF LITERARY THEORIES AND THEIR RELEVANCE IN THE 21ST CENTURY - Sunara; Ida Maulida; Mimin Aminah (DIALEKTIKA: JURNAL BAHASA, SASTRA DAN BUDAYA, 2026)
This abstract explores the evolution of literary theories from Structuralism to Deconstruction and their significance. The introduction highpoints the paradigm shifts over the past century, beginning with Formalism, which emphasizes formal essentials of texts. Subsequently, Structuralism emerged by focusing on language systems, universal patterns, and binary oppositions that organize meaning across cultures. The development continued with Deconstruction, which challenges the notion of fixed meaning by emphasizing language’s inherent instability, ambiguity, and the endless deferment of meaning. The research employs comparative literature analysis to examine these theories’ core concepts differences, and interconnections. Findings show that despite their contrasting approaches, both theories deepen our understanding of how meaning is constructed and interpreted in texts. The analysis emphasizes that these theories remain highly relevant today especially in addressing complex societal issues related to gender identity, digital culture, ecological interconnectedness, and globalization. The conclusion emphasizes that the ongoing evolution from Structuralism to Deconstruction offers vital insights for contemporary literary and cultural analysis, developing more nuanced and flexible interpretative methods that reflect the complexities of modern society.